Major Bleeding after Percutaneous Image-Guided Biopsies: Frequency, Predictors, and Periprocedural Management - Kennedy, Sean A.; Milovanovic, Lazar; Midia, Mehran (Seminars in Interventional Radiology, 2015)
Major bleeding remains an uncommon yet potentially devastating complication following percutaneous image-guided biopsy. This article reviews two cases of major bleeding after percutaneous biopsy and discusses the frequency, predictors, and periprocedural management of major postprocedural bleeding.
Keywords: biopsy; bleed; complications; periprocedural management; interventional radiology